Due diligence: revisiting the heat-aggression association hypothesis. Issue 2 (4th May 2018) - McCarthy, Randy J.
ABSTRACT: Previous research has asserted that individuals hold cognitive associations between the constructs of hot temperatures and aggression. However, subsequent studies have cast doubt on whether these previously used methods reliably produce effects that support this assertion. Thus, the evidence for the existence of a cognitive heat-aggression association is mixed. To test for this hypothetical association using a different method, and to address shortcomings in the previously-used methods, the current studies used a modified Affect Misattribution Procedure to examine whether exposure to heat-related words increased the accessibility of aggressive cognitions. Both a pilot study and a Registered Report showed that exposure to heat-related words increased the accessibility of aggressive cognitions. However, exposure to cold-related words also, and unexpectedly, increased the accessibility of aggressive cognitions. In addition, these results were only found for participants who reported that the primes influenced their Misattribution Task performance. Thus, although the current results found that exposure to heat-related stimuli caused theoretically predicted effects, the overall evidence is somewhat mixed as to whether this is due to a cognitive association between hot temperatures and aggression.